Taking the High Road? Compliance with Commuter Tax Allowances and the Role of Evasion Spillovers - Jörg Paetzold; Hannes Winner (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2014)
We provide first field evidence on evasion spillovers as an important determinant of the individual compliance decision. Exploiting discontinuities in a self-reported commuter tax allowance, we observe a substantial share of taxpayers misreporting their claims. Using exogenous variation in job changes we find that individual evasion decisions are in uenced by the compliance behavior of other co-workers, with job changers from low- to high-cheating companies starting to evade much more after they move. In contrast, movers from high- to low-cheating companies do not alter their reporting. The most likely explanation is information transmission, including increased knowledge about the possibilities for non-compliance.
Keywords: H24; H26; D83; 330; Tax Evasion; Self-Reporting; Spillover Effects; Information Frictions